Integration of wind energy in smart grid: A review - Moulya, P.; Manitha, P. V.; Nair, Manjula G. (AIP conference proceedings, 2024)
The Smart Grid is being improved daily for greater efficiency and is developing as the world’s smartest technology. One method to improve the efficacy or efficiency of smart grid (SG) technology is to integrate alternative renewable energy sources into it. This research has looked at the possibility of integrating alternative energy sources with Smart Grid technology. One of these alternate energy sources is wind power. This study gives an overview of various factors that are considered while integrating wind energy into the smart grid. The efficiency and performance will increase if alternative energy sources can be linked to the Smart Grid based on certain parameters like continuous forecasting and how that is impacting the smart grid, controlling and managing strategies, etc. Several challenges will occur after successful integration of wind energy. The challenges, economic aspects and environmental benefits are addressed in this research. For further improvement of smart grids in the future, the excess energy that is generated needs to be stored in energy storage systems. In this research study, all of these subjects have been covered.